(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2010)
Psychometric tests which otherwise were once w1 obscure apparatus are now increasingly becoming a supportive tool to the Talent Acquisition process and are injecting accuracy iflfo the multi• faceted web of HR. These tests that were earlier ignored due to complexity are now turning out to be the DNA of winning organizations. They aid in the selection of the ’best human asset’ who can late prove to be the right fit in the organization. It defines the competency parameters and the ideal talent to be recruited according to the designed role. This gamut of tests measures the thought processes and aptitude which are prerequisites for job performance. It matches people to job and not job to people. Additionally, it states acceptance level of the candidate to n given role. It helps to minimize subjectivity, nepotism, impulsive judgements and bias which are a few of the inherent flaws in the recruitment process. The tests must be carefully administered and interpreted to ensure that only the ’right ’ is hired. Nonetheless, the analyst must be prudent to verify how long the incumbent would retain himself with the organization.